Research progress of narrative therapy in psychological intervention for cancer patients (叙事疗法在癌症患者心理干预中应用的研究进展) - DONG Ying (董莹); ZHUANG Huan (庄欢); JIANG Guichun (姜桂春) (Association of Integrative Nursing, 2023)
Narrative therapy, as one of the psychological intervention modalities in humanistic medicine, has received increasing attention from scholars in various fields. This paper reviews the concept origin and development of narrative therapy, the application of narrative therapy in psychological interventions for cancer patients, and the advantages and limitations of narrative therapy, with the aim of providing a theoretical basis for clinical research on narrative therapy interventions for cancer patients. (叙事疗法是人文医学心理干预方式之一, 越来越受到各个领域学者的重视。本文从叙事疗法的概念起源及发展、叙事疗法在癌症患者心理干预中的应用、叙事疗法的优势与局限性3个方面进行综述, 以期为叙事疗法干预癌症患者心理情绪的临床研究提供理论基础。)